1992
DOI: 10.1113/jphysiol.1992.sp019354
|View full text |Cite
|
Sign up to set email alerts
|

ATP dependence of Na(+)‐K+ pump of cold‐sensitive and cold‐tolerant mammalian red blood cells.

Abstract: SUMMARY1. The ATP concentration of intact, cold-tolerant (ground squirrel) red cells and cold-sensitive (guinea-pig and human) red cells was monitored by use of the firefly tail, luciferin-luciferase assay. ATP kinetics of the pump in intact red blood cells was investigated by altering cell [ATP] by progressive depletion of ATP in the presence of 2-deoxy-D-glucose and then by measurement of ouabain-sensitive K+ influx at each level of [ATP] at various temperatures between 37 and 5 'C. Na+-K+-ATPase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…extracellular K + or intracellular Na + and ATP). However, we consider this unlikely because substrate concentrations were at saturating levels at room temperature, and previous studies on the Na + /K + -ATPase have shown that the cold increases the apparent affinity for extracellular K + and intracellular Na + (Ellory and Willis, 1982), and for ATP (Marjanovic and Willis, 1992). Furthermore, both the ATPbinding pocket and cation-binding sites of the Antarctic and temperate orthologs are conserved.…”
Section: Based Onmentioning
confidence: 99%
“…extracellular K + or intracellular Na + and ATP). However, we consider this unlikely because substrate concentrations were at saturating levels at room temperature, and previous studies on the Na + /K + -ATPase have shown that the cold increases the apparent affinity for extracellular K + and intracellular Na + (Ellory and Willis, 1982), and for ATP (Marjanovic and Willis, 1992). Furthermore, both the ATPbinding pocket and cation-binding sites of the Antarctic and temperate orthologs are conserved.…”
Section: Based Onmentioning
confidence: 99%
“…-K ? -ATPase activity is just as temperaturesensitive as that of the guinea pig [15]. The capability of ground squirrel cells to maintain low levels of ion leakage during cold exposure appears to be primarily based on the better preservation of intracellular Ca 2?…”
Section: Introductionmentioning
confidence: 95%
“…-K ? -ATPase activity is relatively smaller [15] and rates of passive ion leakage are generally lower in the squirrel cells [16], which together enable preservation of ion gradients at significantly lower metabolic cost. It is worth noting that the capability of maintaining higher Na ?…”
Section: Introductionmentioning
confidence: 98%
“…Because ADP is released in a higher proportion than ATP, a passive leakage was excluded by these authors. Erythrocytes contain large amounts of ATP [28]; the content of ADP is much lower. In each volume of normal blood, the ATP content in the erythrocytes exceeded the releasable platelet ATP by about 50-fold.…”
Section: Discussionmentioning
confidence: 99%